Strength and life of composites - Tsai, Stephen W (Composites Design Tutorial, Aeronautics & Astronautics, Stanford University, 2009)
1- Distribution of micro stresses and ineterfacial tractions in unidorectional composites. 2- Effects of fiber arrangement on mechanical behavior of unidirectional composites. 3- Micro-mechanics of failure (MMF) for continuous fiber reinforced composites. 4- Formulation of long-term creep and fatigue strengths based on ATM. 5- Progressive failure analysis of composites. 6- MAE: An integrated design tool for failure and life prediction of composites. 7- Life prediction of composites using MMF and ATM.